Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1590/0001-3765201720160844
|View full text |Cite
|
Sign up to set email alerts
|

Is Forced Swimming Immobility a Good Endpoint for Modeling Negative Symptoms of Schizophrenia? - Study of Sub-Anesthetic Ketamine Repeated Administration Effects

Abstract: Immobility time in the forced swimming has been described as analogous to emotional blunting or apathy and has been used for characterizing schizophrenia animal models. Several clinical studies support the use of NMDA receptor antagonists to model schizophrenia in rodents. Some works describe the effects of ketamine on immobility behavior but there is variability in the experimental design used leading to controversial results. In this study, we evaluated the effects of repeated administration of ketamine suba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…In comparing mice with rats in Table 1 : while studies often used different parameters such as varied dosing and none of the mouse studies used chronic stress, we can conclude that repeated ketamine is capable of producing either decreases or increases in immobility in the FST in both species, under various experimental conditions, with higher doses such 50 or 100 mg/kg favoring immobility. Regarding different strains of mice or rats: the three studies that used CD-1 and CF-1 mice only found decreases in immobility ( 40 42 ), whereas studies of other albino mouse strains and C57BL/6J mice showed either increases or decreases in immobility depending on the study parameters and strain used ( 39 , 44 48 ). Likewise, Sprague-Dawley or WKY rats were only observed to have decreases in immobility ( 36 , 49 51 , 59 , 60 ).…”
Section: Summary Of Literaturementioning
confidence: 95%
See 4 more Smart Citations
“…In comparing mice with rats in Table 1 : while studies often used different parameters such as varied dosing and none of the mouse studies used chronic stress, we can conclude that repeated ketamine is capable of producing either decreases or increases in immobility in the FST in both species, under various experimental conditions, with higher doses such 50 or 100 mg/kg favoring immobility. Regarding different strains of mice or rats: the three studies that used CD-1 and CF-1 mice only found decreases in immobility ( 40 42 ), whereas studies of other albino mouse strains and C57BL/6J mice showed either increases or decreases in immobility depending on the study parameters and strain used ( 39 , 44 48 ). Likewise, Sprague-Dawley or WKY rats were only observed to have decreases in immobility ( 36 , 49 51 , 59 , 60 ).…”
Section: Summary Of Literaturementioning
confidence: 95%
“…The table consists of mice and rats of both sexes and various strains, ranging in age from adolescents to adults. The studies primarily used racemic (R,S)-ketamine, although one study (42) as noted in the table only used the (S)-ketamine enantiomer. This table comprises the 24 mice and rat studies from our literature search that used repeated administration of ketamine in the FST.…”
Section: Literature Search Detailsmentioning
confidence: 99%
See 3 more Smart Citations